Vibration measurement by use of wavelet transform and temporal carrier technique - Quan, Chenggen (2010)
In this paper, two optical techniques, namely, electronic speckle pattern interferometry (ESPI) and fringe projection, are described for the measurement of a low-frequency vibrating object. The combination of optical interferometry and temporal phase analysis allows the measurement on a continuously deforming object without the spatial phase unwrapping process. A series of speckle or fringe patterns is captured by a high-speed CCD camera, and the intensity variation of each pixel on the recorded images is analysed along the time axis using the temporal wavelet transform method that has the property of adaptive band-pass filtering of a measured signal. However, the wavelet transform method is unable to determine the sign of a phase and it is difficult to analyse a part of the object that is not moving. The sign ambiguity problem can be overcome by adding a temporal carrier in the image acquisition process. In the ESPI, a temporal carrier is introduced by a PZT stage in the reference beam of the interferometer. In the fringe projection technique, a laterally shifted fringe pattern is projected on a vibrating object. After the temporal carrier is removed, the absolute displacement of a vibrating object is obtained without the need for a temporal or spatial phase unwrapping process.